2010
DOI: 10.1186/ar3106
|View full text |Cite
|
Sign up to set email alerts
|

The association between rheumatoid arthritis and periodontal disease

Abstract: Chronic, plaque-associated inflammation of the gingiva and the periodontium are among the most common oral diseases. Periodontitis (PD) is characterized by the inflammatory destruction of the periodontal attachment and alveolar bone, and its clinical appearance can be influenced by congenital as well as acquired factors. The existence of a rheumatic or other inflammatory systemic disease may promote PD in both its emergence and progress. However, there is evidence that PD maintains systemic diseases. Neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
2
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(176 citation statements)
references
References 57 publications
3
163
2
8
Order By: Relevance
“…당뇨병, 관상동맥성 심 장질환, 심근경색증, 뇌졸중, 대사증후군 및 류마티스 관절 염과 같은 전신질환과 관련되어 있으며 [3][4][5][6][7][8] , 호르몬 불균형 및 면역기능의 변화는 치주질환의 위험증가에 영향을 준다 3,9) . 류마티스 관절염은 전 세계 인구의 약 1% 정도가 가지고 있 는 자가면역질환으로 3,10,11) , 전신성 면역기능의 변화에 더하 여 활막에서 염증성 세포침윤의 축적을 특징으로 한다 12) .…”
Section: 서 론unclassified
“…당뇨병, 관상동맥성 심 장질환, 심근경색증, 뇌졸중, 대사증후군 및 류마티스 관절 염과 같은 전신질환과 관련되어 있으며 [3][4][5][6][7][8] , 호르몬 불균형 및 면역기능의 변화는 치주질환의 위험증가에 영향을 준다 3,9) . 류마티스 관절염은 전 세계 인구의 약 1% 정도가 가지고 있 는 자가면역질환으로 3,10,11) , 전신성 면역기능의 변화에 더하 여 활막에서 염증성 세포침윤의 축적을 특징으로 한다 12) .…”
Section: 서 론unclassified
“…Over 47% of American adults suffer from periodontitis, the most common infectious disease in humans (3). In addition to dental diseases, recent studies have also reported that P. gingivalis is related with systemic diseases, such as cardiovascular diseases (4), decreased kidney function (5), and rheumatoid arthritis (6). The bacterium does not ferment carbohydrates, but grows under strict anaerobic conditions using proteinaceous substrates as carbon and energy sources.…”
mentioning
confidence: 99%
“…One hypothesis is that these microorganisms trigger the development of RA in individuals who carry genetic susceptibility factors to the disease (Tobon et al, 2010); however, the role for microorganisms as initiating factors of RA remains controversial. There are findings supporting the hypothesis that oral infections play a role in RA pathogenesis, while of special importance are the impact of periodontal pathogens, such as Porphyromonas gingivalis on citrullination, and the association of Periodonditis (PD) in RA patients with seropositivity toward RF and ACPA (Detert et al, 2010). …”
Section: Gene-to-environment Interactionsmentioning
confidence: 77%